Evidence of nutritional support in patients with COVID-19 diagnosis (Research, Society and Development, 2020)
In December 2019, Wuhan, capital of Hubei, province of China, faced an outbreak similar to pneumonia, of unknown cause, with clinical presentations similar to a viral infection. In one month, samples from the lower respiratory tract were subjected to a sequencing analysis, characterizing the condition as resulting from coronavirus, receiving the name of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) or COVID-19, as designated by World Health Organization. Since then, the disease has affected countries around the world, which are still looking for an effective treatment for the disease. Bearing in mind that the integrity of the immune system is crucial for the recovery and improvement of the prognosis of patients affected by the infection, the adequate supply of nutrients is essential for its maintenance, in addition to the fact that the inadequacy of the nutritional status can increase the predisposition to secondary infections, hospital complications, and morbidity and mortality rates. Given this, the present study corresponds to a literature review, compiling the main evidence that vitamins and minerals can act as enhancers of the proposed treatments and directly or indirectly assist the recovery of COVID-19 patients.